2014
DOI: 10.7860/jcdr/2014/8455.4641
|View full text |Cite
|
Sign up to set email alerts
|

Neck Circumference and Cardio-Metabolic Syndrome

Abstract: Background: Only few studies about neck circumference (NC) as a measure of cardio metabolic syndrome available from India. Study was conducted to establish an association between neck circumference and cardio metabolic syndrome. Material and Methods:Cross-sectional study was conducted in a tertiary care hospital in South India. NCEP: ATPIII 2001 guideline was used for diagnosis of Cardio-metabolic syndrome among subjects. Neck circumference was measured and it was correlated with Cardio-metabolic syndrome.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
(13 reference statements)
3
7
0
Order By: Relevance
“…The differences are not unexpected given the relationship between NC with age, BMI and WC. Consistent with previous studies men had a higher mean NC [14,18,21].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The differences are not unexpected given the relationship between NC with age, BMI and WC. Consistent with previous studies men had a higher mean NC [14,18,21].…”
Section: Discussionsupporting
confidence: 92%
“…A study conducted among the Turks [11,13] and Saudi Arabs [14] revealed that NC had positive correlation with indices of general and central obesity. Similar studies among the Chinese [15][16][17], Indians [18,19], Indonesians [20], and other Asian populations [21], also confirmed the positive association between NC with established anthropometric indices and cardiovascular risk factors. Specifically, Fan et al, [22] examined the relationship between NC and arterial hypertension, and found that NC predicted blood pressure, independent of other anthropometric indices.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…Similarly, NC with metabolic syndrome correlated better among females than males. The cross-sectional study was conducted in a tertiary care hospital in South India, showed that men with NC >37 cm and women with NC >34 cm are more prone to cardiometabolic syndrome and require additional evaluation [ 10 ]. A study of 3182 diabetic Chinese patients showed that NC correlated positively with BMI, WC, and metabolic syndrome [ 11 ].…”
Section: Introductionmentioning
confidence: 99%